Coins in Rhodes : from the monetary reform of Anastasius I until the Ottoman conquest (498-1522) - Kasdagli, Anna-Maria (Archaeopress Publishing Ltd, 2018)
'Coins in Rhodes' presents the Byzantine and medieval coins collected by Greek archaeologists in Rhodes over a period of more than sixty years. It includes lists of excavated land plots, stray finds, an illustrated catalogue of all the Byzantine and local coins up to 1309, and a representative sample of the Hospitaller petty coins as well as all the Western coins found.